Devil's food cake murder [compact disc, unabridged] - Fluke, Joanne, 1943- (Fluke, Joanne, 1943- Hannah Swensen mystery., 2011)
This novel finds the residents of Lake Eden, Minnesota, buzzing with activity. Perhaps busiest of all is Hannah Swensen, proprietor of The Cookie Jar, who is experimenting with a devil's food cake recipe. But no matter how hectic times may be, Hannah can always find time to help a friend--particularly a dead one.